Development and Validation of a Gas Chromatography−Flame Ionization Detection Method for the Determination of Epoxy Fatty Acids in Food Matrices - Mubiru, Edward; Shrestha, Kshitij; Papastergiadis, Antonios; Meulenaer, Bruno De (Journal of Agricultural and food chemistry, 2014)
A reliable and suitable method for the determination of epoxy fatty acids in various food matrices based on the Bligh and Dyer lipid extraction procedure was developed and validated. The method involves the use of a methylated epoxy fatty acid as internal standard (IS), extraction of the analytes from the matrices followed by room temperature methylation, a three- step solid phase extraction (SPE) separation of the fatty acid methyl esters (FAMEs), and detection with gas chromatography− flame ionization detection (GC-FID). The method was validated in four different food matrices chosen as model systems, namely, vegetable oils, unprocessed pork, fried potato crisps, and infant formula. The extraction technique allows the method to be applied for routine analysis of a large amount of samples. Intraday repeatability ranged from 1 to 19%, and interday reproducibility ranged from 2 to 9%. The limit of quantification (LOQ) ranged from 3.32 to 20.47 μg g−1 of sample with recoveries ranging from 94 to 115%. The results verify the accuracy and reproducibility of the analytical technique and its ability to provide reliable quantification of epoxy fatty acids. Finally, levels of epoxy fatty acids in several food products on the Belgian market were screened and are presented.
Keywords: Lipid oxidation; Epoxy fatty acids; Fatty acid methyl esters; Gransesterification; Bligh and Dyer